El Reglamento, ¿acto administrativo en el Derecho peruano? - Baca Oneto, Víctor Sebastian; Abruña Puyol, Antonio (Revista de Derecho, 2019)
This essay focuses on the difference between normative acts [Rules] and non normative acts [adjudications] of the Public administration and, despite the verification of this difference, is possible to include them in the only category of administrative acts, defined as Public Administration’s declarations that produce juridical effects in exercise of an administrative legal power. From a doctrinal perspective, this is the conclusion of the authors, to which they come after analyzing the criteria proposed to distinguish the normative acts (general regulations or Rules) of non normative acts (single decisions or adjudications), and of highlighting their similarities. About Peruvian Law, the authors analyze the Law 27444, Administrative General Procedure Act, in which they can find arguments to affirm that the Rules are also administrative acts [adjudications], though this norm will not be applied to them fully, because they are abstract and ordinamental measures. This last criterion could be used to distinguish between normative and non normative administrative acts, since in the administrative area is possible to affirm that those acts belong to one or another category «by nature», and not only form a formal criterion.